The rise of Chemical Peeling in 19th‐century European Dermatology: emergence of agents, formulations and treatments. (25th May 2020) - Borelli, C.; Ursin, F.; Steger, F.
Abstract: Background: Considering the increasing number of chemical peeling applications, also the interest in the history of chemical peelings and agents, has grown in dermatology. Research ascribes the first use of phenol as a chemical peeling agent to William Tilbury Fox (1836–1879) in 1871. Furthermore, Ferdinand von Hebra (1847–1902) is said to describe the properties of various peeling agents in 1874, and Paul Gerson Unna (1850–1929) adds resorcinol and trichloroacetic acid in 1882. Objective: To identify the first mentions of chemical peeling applications and agents in 19th‐century dermatology. Methods: Nineteenth‐century dermatologists were identified by an examination of literature of the last 30 years on the history of chemical peeling. Systematic examination of the medical textbooks of Hebra, Fox and Unna was conducted. It was proved whether the mentioned agents were used for chemical peeling applications. Results: The skin peeling property of phenol was already discovered by its first describer, the chemist Friedlieb Ferdinand Runge (1795–1867) in 1834. The Viennese dermatologist Hebra described phenol as a chemical peeling agent in 1860. Hebra and his associate Moriz Kaposi (1837–1902) stated that 'Lotio carbolica' was already used in London. Fox used phenol mostly as a disinfectant and not for chemical peelings since 1869. Unna described the chemical peeling property of salicylic acid in 1882 and gave the most comprehensive account of chemical peels of the 19th century in 1899. Unna also introduced the Gutta‐percha plaster with salicylic acid and phenol. Around 1900, Unna was famous for his peeling paste with resorcinol in Germany. Conclusions: A new chronology of the introduction of chemical peeling in dermatology can be drawn from the results. The German‐speaking dermatology pioneered the treatment of skin diseases with chemical peelings as well as for aesthetical purposes 21 years earlier than hitherto known.